Effect of New Zealand Blackcurrant Powder on Skin Emission of Volatile Organic Compounds in Middle Aged and Older Adults (P06-092-19). (13th June 2019) - Willems, Mark; Todaka, Michihito; Banic, Milena; Cook, Matthew; Sekine, Yoshika
Abstract: Objectives: Volatile organic compounds (i.e., VOCs) emanating from the human skin are used to detect disease biomarkers and causes of body odour. Seven-day intake of New Zealand blackcurrant (NZBC) powder reduced skin emission of 2-nonenal, a lipid peroxidation compound responsible for body odour in older adults. Anthocyanin-induced bioavailability of plasma metabolites by intake of NZBC may affect the production of VOCs. In the present study, we examined the effect of 7-day NZBC powder intake on the skin emission of 76 VOCs. Methods: Fourteen Caucasian adults (9 males, age: 55 ± 5 yr) volunteered. Participants consumed NZBC powder for 7 days (Sujon Berries, NZ, 6 g·day -1 with 138.6 mg anthocyanin, 49 mg Vit C, 5.2 g of carbohydrates and total phenolic content of 271.6 mg per serving). Two hours after the last intake, a passive flux sampler with trapping media (MonoTrap®, DCC18, GL Science, Japan) was applied to the skin in the base of the neck for one hour, and gas chromatography-mass spectrometry was used for media analysis (Kimura et al., 2016). Participants did not use hot water or soap for 48 hrs on the skin sampling location. Dietary anthocyanin intake was quantified using a food frequency questionnaire. Data were analysed with paired, two-tailed t-test and effect size (Cohen's d) was calculated. Results: Decreases in skin emission were observed for acetic acid (−57%, P = 0.006, d = −1.26), 2-hexanone (−47%, P = 0.031, d = −0.86), 6-methyl-5-hepten-2-one (−93%, P = 0.005, d = −1.23), benzaldehyde (−86%, P = 0.004, d = −0.96), allyl methyl sulfide (−35%, P = 0.015, d = −0.98) and increases for γ-octanolactone (+65%, P = 0.023, d = 0.98) and γ-decanolactone (+47%, P = 0.015, d = 1.11). For these VOCs, there was no significant correlation between daily anthocyanin intake and baseline values. A trend for a decrease was observed for isovaleraldehyde, hexanal and 2-pentanone and an increase for heptanoic acid and γ-nonanolactone, all 0.05 < P < 0.1. Conclusions: Anthocyanin-containing NZBC powder can change the emanation of some volatile organic compounds in human skin. Analysis of volatile organic compounds in human skin following nutritional interventions can address the impact of dietary components to affect human body odour and health. Funding Sources: Sujon Berries (Nelson, NZ) provided supplements. Support for conference attendance was obtained from Blackcurrant New Zealand Inc. (NZ).